Biomechanical response of intact, degenerated and repaired intervertebral discs under impact loading – Ex-vivo and In-Silico investigation. (21st March 2018) - Nikkhoo, Mohammad; Wang, Jaw-Lin; Parnianpour, Mohamad; El-Rich, Marwan; Khalaf, Kinda
Abstract: Understanding the effect of impact loading on the mechanical response of the intervertebral disc (IVD) is valuable for investigating injury mechanisms and devising effective therapeutic modalities. This study used 24 porcine thoracic motion segments to characterize the mechanical response of intact (N = 8), degenerated (Trypsin-denatured, N = 8), and repaired (Genepin-treated, N = 8) IVDs subject to impact loading. A meta-model analysis of poroelastic finite element simulations was used in combination with ex-vivo creep and impact tests to extract the material properties. Forward analyses using updated specimen-specific FE models were performed to evaluate the effect of impact duration. The maximum axial stress in the IVDs, Von-Mises stress in the endplates, and intradiscal pore pressure (IDP) were calculated, under a 400 N preload, subject to a sequence of impact loads for 10 impact durations (10–100 ms). The results were in good agreement with both creep and impact experiments (error < 10%). A significant difference was found in the maximum axial stress between the intact and degenerated disc groups. The IDP was also significantly lower in the degenerated disc group. The Von Mises stress in the adjacent endplates significantly increased with degeneration. It is concluded that the disc time-dependent response significantly changes with disc degeneration. Cross-linker Genipin has the potential to recover the hydraulic permeability and can potentially change the time dependent response, particularly in the IDP. This is the first study, to our best knowledge, which explores the effect of impact loading on the healthy, degenerated and repaired IVD using both creep and impact validation tests.